Kualitas Fisik Dan Bakteriologi Udara Dalam Ruang Terhadap Gangguan Kesehatan Di Dinas Perpustakaan Dan Kearsipan Provinsi Maluku - Damayanti Sima Sima Sohilauw; M Fadly Kaliky; Fitria Tuharea (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
The Maluku Province Library and Archives Service found that the physical quality of the space did not meet the requirements, such as no ventilation, air conditioning and only a few windows that were open. This causes a lack of air coming in from outside so that employees feel hot and stuffy in the room. The aim of this research is to determine the physical and bacteriological quality of indoor air on health problems in the Maluku Province Library and Archives Service. The method used in this research is descriptive to determine the physical and bacteriological quality of indoor air on health problems at the Maluku Province Library and Archives Service. The population in this research is the entire library and archives space of Maluku Province. The samples in this research were 2 sample points, namely the reading room and the staff room of the Maluku Province Library and Archives Service. The research results show that lighting, temperature and germ numbers meet the requirements, while humidity does not meet the requirements. In accordance with Minister of Health Regulation No. 2 of 2023 concerning Environmental Health. The conclusion is that lighting, temperature and germ numbers meet the requirements, while humidity does not meet the requirements